San Josemaría Escrivá de Balaguer y la devoción al Amor Misericordioso (1927-1935) / St. Josemaría Escrivá and the devotion to the Merciful Love (1927-1935) - Federico M. Requena (Studia et Documenta)
This study offers an introductory overview of Saint Josemaría Escrivá’s relationship with the Merciful Love, a devotion diffused in Spain during the 1920’s and 1930’s by the writings of the French nun of the Visitation Order, María Teresa Desandais. St. Josemaría’s relationship with the Merciful Love Movement is the story of a process which ran parallel to the beginnings of Opus Dei and to the development of two dimensions which were inseparable and of great importance in his spiritual life: divine filiation and spiritual childhood.